catena-Poly[[trimethyltin(IV)]-μ-cyclohex-3-ene-1-carboxylato] - Yun Ren; Rufen Zhang; Yang Shi (Acta Crystallographica Section E, 2010)
The title compound, [Sn(CH3)3(C7H9O2)]n, forms an extended zigzag chain structure propagating parallel to [010]. The Sn atom is in a slightly distorted trigonal-bipyramidal coordination environment with two carboxylate O atoms in the axial and the three methyl groups in equatorial sites. The cyclohexene ring has a distorted half-boat conformation. There is an intramolecular C—H...O hydrogen bond.